Jornalismo Imersivo: Dez anos de pesquisa e produções : Immersive Journalism: Ten years of Research and Production (International Journal on Stereo & Immersive Media, 2020)
This article aims to review the first ten years of research on immersive journalism, making a connection with journalistic practice. It starts with the initial formulation of the concept presented by De la Peña et al. (2010). A qualitative approach methodology, combined with a quantitative approach, is explored both with bibliographic research and a bibliometric analysis of academic publications on the concept. In this way, a mapping of investigations on immersive journalism in Portuguese, English and Spanish is made, and it is proposed to categorize these works considering the respective approaches. There are also professional immersive products explored as an empirical corpus in publications. Among the results, it is concluded that there is a scarcity of applied research and a demand for a deeper treatment of immersive journalism, instead of purely descriptive approaches. There is still a gap, not yet addressed academically, between the context from which the concept of immersive journalism was developed and the practice reported in scientific publications.Resumo:Este artigo tem como objetivo fazer uma revisão dos primeiros dez anos de pesquisa do jornalismo imersivo, fazendo uma relação com a prática jornalística. Parte-se da formulação inicial do conceito apresentado no trabalho de De la Peña et al. (2010). Explora-se com uma pesquisa bibliográfica uma metodologia de abordagem qualitativa, combinada com uma abordagem quantitativa através de uma análise bibliométrica das publicações acadêmicas sobre o conceito. Desta forma, elabora-se um mapeamento das investigações sobre o jornalismo imersivo em português, inglês e espanhol, e propõe-se uma categorização destes trabalhos considerando as respectivas abordagens. Observam-se também produtos imersivos profissionais explorados como corpus empírico nas publicações. Entre os resultados conclui-se que há uma escassez de pesquisas aplicadas e uma demanda por um tratamento mais aprofundado do jornalismo imersivo, para além de abordagens meramente descritivas. Regista-se ainda um desfasamento, ainda não abordado academicamente, entre o contexto a partir do qual o conceito de jornalismo imersivo foi desenvolvido e a prática relatada em publicações científicas.